Incidencia de los estándares de gestión escolar para el mejoramiento de la calidad de la educación en la escuela Ramón Páez, del cantón Latacunga en el período lectivo 2013- 2014 - Guanotasig Catota, Mayra Cecilia (2015)
This research is about the teacher’s knowledge importance at school management standars; it is base on the virtual guide development for improvement of educational quality in “Ramón Páez” at Patután neighborhood. In this research a survey to the educational actors (teachers, students and parents) was applied, which helped to investigate about school management standars to improve the institution’s education, it was carried out, in order to know about the educational management standars and it gives a good use of them, as a good school management organized labor facilitates and promotes the development of basic skills and citizens, since thereby improving the quality of education that will be achieved….